Effect of biocompost fermented by Trichoderma spp. on the growth of soybean (Glycine max L) - Suhaili, Suhaili; Suryanto, Ribut; Wahyuni, Ida (Jurnal Agrotek Ummat, 2023)
National soybean production is not enough to meet the national demand for soybeans so there is a need to increase the production of this commodity because it is needed as a raw material for various processed products. The utilisation of dry land as soybean cultivation land is still lacking. This is due to several factors, namely cultivation techniques, and limited fertilisation. So the use of cultivation techniques by applying biocompost fertiliser is one approach to improve soil nutrients and also the use of Trichoderma spp. bacteria helps soybean plants to avoid wilt disease.  This study aims to determine the growth response of several varieties of soybean on dry land by applying biocompost fermented by Trichoderma spp. The method used in this research is an experimental method carried out by manipulating the object of research and the existence of controls. The research was conducted on dry land in Giri Tembesi Village, Gerung Sub-district, West Lombok Regency, the soil type of the experimental site was regusol soil with a pH of 5.7 and organic matter moisture content of 0.77%. The results showed that the application of biocompost to several varieties of soybean has not been able to spur plant growth but in general can adapt to dry land. Differences in soybean varieties resulted in significantly different growth responses in plant height, number of leaves, number of branches, flowering age and weight of 100 soybean seeds. However, there is no significant difference in the application of biocompost on the vegetative and generative growth of soybean in dryland which is thought to be caused by the dose of biocompost given is not optimal. Therefore, further research is needed to obtain the optimal dose of biocompost.